2019
DOI: 10.4322/2526-8910.ctoao1125
|View full text |Cite
|
Sign up to set email alerts
|

A construção da co-ocupação materna na Unidade de Terapia Intensiva Neonatal

Abstract: Introduction: The term co-occupation has been used by occupational therapists to define the implicit involvement of two or more individuals in an occupation. In this perspective, maternal care is considered a co-occupation, and occupational therapists seek to promote the insertion of the mother in the Neonatal Intensive Care Unit (NICU), maternal guaranteeing autonomy and independence in the care of the baby. Objective: To analyze how the construction of maternal co-occupation in the NICU takes place. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 12 publications
0
7
0
20
Order By: Relevance
“…Confirmando, assim, a falta de protagonismo materno visto em trabalhos, mas que deveriam ecoar como pontos de mudança, revendo o papel materno, não mais como receptora de mensagens, mas também de emissora (Fraga et al, 2019) Logo, trazer a mãe para ocupar seu lugar de direito é uma estratégia de cuidado, pois parte da premissa que a mãe realizará sua co-ocupação na UTIN. Essa co-ocupação com o envolvimento implícito de dois ou mais indivíduos, que estão em uma ocupação, permite que cada pessoa influencie a outra.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Confirmando, assim, a falta de protagonismo materno visto em trabalhos, mas que deveriam ecoar como pontos de mudança, revendo o papel materno, não mais como receptora de mensagens, mas também de emissora (Fraga et al, 2019) Logo, trazer a mãe para ocupar seu lugar de direito é uma estratégia de cuidado, pois parte da premissa que a mãe realizará sua co-ocupação na UTIN. Essa co-ocupação com o envolvimento implícito de dois ou mais indivíduos, que estão em uma ocupação, permite que cada pessoa influencie a outra.…”
Section: Discussionunclassified
“…Essa co-ocupação com o envolvimento implícito de dois ou mais indivíduos, que estão em uma ocupação, permite que cada pessoa influencie a outra. Assim, a mãe realizaria o cuidado que já era dela, mas como processo de co-ocupação e protagonista do cuidado do filho, sendo preparada, inclusive para a alta da UTIN (Fraga et al, 2019).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Throughout the hospitalization, the mother was happy to be involved in care activities, such as "breastfeeding", "changing the diaper" and "bathing the baby". Fraga et al (2019) identified that allowing maternal involvement in caring for their preterm child enables ownership over time and mothers show satisfaction in exercising them. The role of the occupational therapist proves to be important in intervening in the environment and facilitating the person's participation in daily occupations (Fisher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%